Marchiafava-Bignami syndrome with Wernicke-Korsakoff overlap: A rare case of post-binge encephalopathy in a chronic alcoholic - Gupta, Namit; Gurjar, Pankaj; Daga, Ayushi; Rani, Shilpi (Indian Journal of Case Reports, 2026)
Marchiafava-Bignami syndrome (MBS) is a rare demyelinating disorder of the corpus callosum, predominantly seen in chronic alcoholics and malnourished individuals. It is characterized by demyelination and necrosis of the corpus callosum, often presenting with neuropsychiatric manifestations. We report a 32-year-old male with a long history of alcohol abuse who developed altered sensorium and cognitive impairment following a binge-drinking episode. Magnetic resonance imaging revealed diffuse T2/fluid-attenuated inversion recovery hyperintensities involving the genu and splenium of the corpus callosum, bilateral thalami, internal capsules, and brainstem, suggestive of MBS with associated Wernicke-Korsakoff overlap. Cerebrospinal fluid analysis and oligoclonal bands were negative. The patient showed partial improvement in sensorium following thiamine therapy. This case highlights the importance of early recognition of alcohol-related demyelinating encephalopathies to prevent irreversible neurological damage.